Pendampingan Pengelolaan Sumber Rujukan Penelitian melalui Software Zotero untuk Mahasiswa Calon Guru di Universitas Ibrahimy - Moh. Atikurrahman; Saiful Saiful (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This community engagement program aimed to improve pre-service teachers' ability to manage research references using Zotero software through a participatory training and mentoring approach, involving 67 students from four study programs at Universitas Ibrahimy — Islamic Education (27 students), Arabic Language Education (20 students), Early Childhood Islamic Education (8 students), and Mathematics Education (12 students) — assisted by two supervising lecturers, with activities covering software installation, library management, citation integration in Microsoft Word, and structured evaluation. Average mastery rose from 38.75% before training to 87.50% afterward (a gain of 48.75 percentage points), attendance averaged 94% across all sessions, and 85% of participants reported satisfaction with the program, alongside reduced citation errors and improved ability to compile systematic bibliographies. While these results indicate that Zotero-based mentoring effectively strengthens students' academic writing quality and digital literacy, long-term effectiveness depends on continuous monitoring and institutional support to ensure consistent adoption beyond the training period, positioning this program as a replicable model for technology-based capacity building in higher education.